Hubungan Keceradasan Emosional dengan Kemampuan Beradaptasi Dalam Pembelajaran Daring di SMPN 1 Kota Bogor - Siti Hajar Utami; Maemunah Sa'diyah (LPPM Institut Nasional Laa Roiba Bogor, 2022)
This study aims to describe the relationship between emotional intelligence and adaptability in online learning in class VII at SMPN 1 Bogor City. The method used in this research is a quantitative method with a correlation approach. The sample in this study was 25% of the total population of 288 (72 respondents) using simple random sampling technique. This data collection technique uses a questionnaire (questionnaire). Emotional intelligence using a questionnaire with the results of the validity test of 15 statement items, there are 14 statements that are proven valid and the reliability test results of the coefficient of 0.750 are declared reliable. While the ability to adapt in online learning using a questionnaire with the results of a valid test of 15 statements proved valid and a reliability test result of 0.762 was declared reliable. Prerequisite test is done by normality test and linearity test. Data analysis used the analyze correlate-bivariate technique on SPSS 26 with a significance level of 5%. The results showed that there was a positive and significant relationship between emotional intelligence and adaptability in online learning as indicated by the r-count value of 0.623 which means it has a strong correlation. And r-count is greater than r-table (0.623 > 0.232), then Ho is rejected and Ha is accepted. And the two variables also have a significant relationship because the significant value (p-value) is 0.000 <0.05, then Ho is rejected and Ha is accepted. Keyword: Emotional Intelligence, Adaptability, Online Learning